1999
DOI: 10.1016/s0960-894x(99)00423-0
|View full text |Cite
|
Sign up to set email alerts
|

Acylcarnitine analogues as topical, microbicidal spermicides.

Abstract: Acylcarnitine analogues, (+)-6-Carboxylatomethyl-2-alkyl-4,4-dimethylmorpholinium (Z-n, where n = the number of carbons in the alkyl chain), synthesized in multi-gram quantities show in vitro activities as spermicides, anti-HIV agents, and inhibitors of the growth of Candida albicans. Activity improves with increasing chain length. Compound Z-15 is a candidate for further study as a topical, microbicidal spermicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…On the basis of dose-and time-response data, the SL ethyl ester with a 20-carbon chain length displayed lower spermicidal activity than the SL hexyl ester with a 24-carbon chain length. This phenomenon has been reported for two other series of spermicidal lipids, albeit studying longer chains (22,33). Analysis of the ring-opened SL free acid (18 carbons) and the alkyl ester (19 to 24 carbons) structures shows that alkylation also increases cytotoxicity while decreasing antiviral activity.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…On the basis of dose-and time-response data, the SL ethyl ester with a 20-carbon chain length displayed lower spermicidal activity than the SL hexyl ester with a 24-carbon chain length. This phenomenon has been reported for two other series of spermicidal lipids, albeit studying longer chains (22,33). Analysis of the ring-opened SL free acid (18 carbons) and the alkyl ester (19 to 24 carbons) structures shows that alkylation also increases cytotoxicity while decreasing antiviral activity.…”
Section: Discussionsupporting
confidence: 67%
“…Serial twofold dilutions of the test compounds in 0.9% NaCl were incubated with semen aliquots for 30 seconds. Motility was evaluated under the microscope during the first incubation and after dilution in buffer and further incubation for 1 h. Only those dilutions that immobilized 100% of the spermatozoa pass the test (22). Results were expressed as minimum effective concentrations (MECs) (also called ED100).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With these ideas in mind, we discovered that a homologous series of compounds of type Z, where Z15 HPC, are active as anti-HIV spermicides and as anti-Candida agents, when compared to commercial products [52]. We later found that Z14 and Z15 have excellent antigonorrhea, antichlamydial, and anti-Haemophilus activities [53].…”
Section: Amphiphilic Zwitterions 31 Amphiphilic Zwitterions As Topmentioning
confidence: 99%
“…Novel acylcarnitine analogues have proved to be potent inactivators of HIV as well as sperm [9], without showing significant vaginal irritation potential. These compounds are also effective against C. trachomatis, N. gonorrhoeae, Haemophilus ducreyi, and Candida albicans [10].…”
Section: Microbicidal Inactivatorsmentioning
confidence: 99%